(untitled) (Filologia e Linguística Portuguesa, 2011)
This paper is an analysis of an official letter from the eighteenth century, detailing lexias showing the cultural aspects of the captaincy of Goiás in the colonial period of Brazil, upheld by Salles (1992). The semi-diplomatic edition of the letter was based on criteria available in Megale and Toledo Neto (2005) and its objective was to compose a reliable source of linguistic research. We also comment on the official letter and on how the social hierarchy of the period influenced the structure of discourse (Berlinck; Barbosa; Marine, 2008). And, finally, we highlight some graphematic variation in the text, indicating that official documents are also helpful in studies of linguistic variation, because the writing contained in them reveals the influence of orality (Mattos and Silva, 2008).